Improving the performance of pyramid solar distiller using dangled cords of various wick materials: Novel working mechanism of wick. (December 2021) - Alawee, Wissam H.; Essa, F.A.; Mohammed, Suha A.; Dhahad, Hayder A.; Abdullah, A.S.; Omara, Z.M.; Gamiel, Y.
Abstract: In this work, a new idea of using the wick material inside the solar distiller is provided. This paper introduces a new mechanism of using wick materials inside the solar stills. The main aim of the proposed mechanism is to improve the solar still productivity. This was achieved by creating specified number of cracks on a parallel upper basin liner with an offset of 3 cm from the original basin liner of the solar still. The basin saline water was kept at 2.5 cm over the original basin liner. Besides, the upper basin liner was covered by a wick material. Moreover, wick cords were dangled from the cracks and edges of the upper basin liner to withdraw the saline water and keep the wick surface wet all the time. This design prevents wasting energy and optimizes the use of wick inside the solar still because the wick cords withdraw an amount of saline water equals to the evaporated quantity without excessing or removing hot water. So, there is no loss of hot water. The tested parameters in this study were the different types of wick materials (cotton wick and jute wick) and different numbers of cracks/cords (9, 16, 25, and 35 cords). Experimental results obtained that the thermal performance of the cords wick solar still was superior than that of the conventional solar still. In addition, using the jute wick provided constantly better performance of cords wick solar still than the cotton wick material. Moreover, the best performance of cords wick solar still was obtained at 25 cords, where the increase in productivity of cords wick solar still over the conventional solar still was 122 and 118% when using jute and cotton wick, respectively. Also, the daily thermal efficiency of cords wick solar still was 53% (at 25 cords) compared to 34.5% for the conventional solar still.